Directed evolution of the transcriptional regulator DntR: isolation of mutants with improved DNT-response. - Rosa Lönneborg; Edina Varga; Peter Brzezinski (PLoS ONE, 2012)
The transcriptional regulator DntR, which previously has been isolated from bacterial strains capable of degrading 2,4-dinitrotoluene (DNT), was engineered in order to improve the ability to detect DNT. A directed evolution strategy was employed, where sequence diversity first was created by random mutagenesis in three subsequent rounds, followed by recombination of previously selected mutants. A gfp gene was used as a reporter for transcriptional activity mediated by DntR and cells with higher GFP expression after addition of DNT were sorted out using fluorescence-activated cell sorting (FACS). A DntR mutant, which displayed 10 times higher induction levels than wild-type DntR in response to DNT was isolated. This mutant still maintained low levels of gfp expression in the absence of DNT. The detection limit was ∼10 µM, a 25-fold improvement compared to wild-type DntR. The functional role of some substitutions found in this clone is discussed in the framework of the structural changes observed when comparing the recently determined structures of DntR with and without bound inducer ligand.